RELIGIUSITAS DENGAN MOTIVASI KERJA GURU DI SEKOLAH DASAR KABUPATEN HALMAHERA BARAT - Frangki Reinaldo Laike; Doddy Hendro Wibowo (Journal of Innovation Research and Knowledge, 2024)
This study aims to measure the level of religiosity of Elementary School teachers in West Halmahera Regency. The benefits of this study are to develop psychology, especially in the field of educational psychology related to religiosity and teacher work motivation. The research method used is quantitative using a correlational study design. The location of the study is Elementary School (SD) in West Halmahera Regency. The results of data analysis show that there is a relationship between religiosity and work motivation, with a correlation coefficient of 0.240 with a significance value of 0.009> 0.05. From these results it can be concluded that there is a significant positive relationship between religiosity and teacher work motivation in West Halmahera Regency. This means that the higher the level of teacher religiosity, the higher the level of work motivation they have. Conversely, if the level of teacher religiosity is low, then the work motivation they have also tends to be lower